2019
DOI: 10.3390/plants8060160
|View full text |Cite
|
Sign up to set email alerts
|

Waterlogging Causes Early Modification in the Physiological Performance, Carotenoids, Chlorophylls, Proline, and Soluble Sugars of Cucumber Plants

Abstract: Waterlogging occurs because of poor soil drainage and/or excessive rainfall and is a serious abiotic stress affecting plant growth because of declining oxygen supplied to submerged tissues. Although cucumber (Cucumis sativus L.) is sensitive to waterlogging, its ability to generate adventitious roots facilitates gas diffusion and increases plant survival when oxygen concentrations are low. To understand the physiological responses to waterlogging, a 10-day waterlogging experiment was conducted. The objective o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
66
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(79 citation statements)
references
References 52 publications
12
66
1
Order By: Relevance
“…Proline acts as an osmoprotectant molecule, maintaining and improving the water status of plants. Proline also acts as an antioxidant, protecting the cell from free radical damage and maintaining the cellular environment for the better synthesis of biomolecules that play a role in stress adaptation [40]. Unlike many other studies, Pro content was decreased in plants grown under prolonged waterlogging (6 and 8 days), which was supported by other studies [41,42,43,44].…”
Section: Discussionmentioning
confidence: 59%
“…Proline acts as an osmoprotectant molecule, maintaining and improving the water status of plants. Proline also acts as an antioxidant, protecting the cell from free radical damage and maintaining the cellular environment for the better synthesis of biomolecules that play a role in stress adaptation [40]. Unlike many other studies, Pro content was decreased in plants grown under prolonged waterlogging (6 and 8 days), which was supported by other studies [41,42,43,44].…”
Section: Discussionmentioning
confidence: 59%
“…Our findings coincide with the earlier report, in which waterlogging (hypoxia) adversely affected the development of root biomass and subsequently led to compromised plant growth and development ( de San Celedonio et al, 2016 ). Under hypoxia conditions, dispersal of oxygen is 320K times lower than in aerated soils, which ultimately hinders plant growth ( Barickman et al, 2019 ; da Ponte et al, 2019 ). However, our findings revealed that the use of Si and SiNPs could improve the growth and dry biomass of muscadine grape plants.…”
Section: Discussionmentioning
confidence: 99%
“…Oxygen deficiency limits plants’ gas exchange attributes and results in an impaired photosynthetic activity ( He et al, 2018 ; Barickman et al, 2019 ). In this study, hypoxia stress caused a reduction in green pigments, stomatal conductance, and internal CO 2 concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Different plant processes, i.e., cytoplasmic pH, cellular energy, stem elongation, and adventitious root formation decreases. In addition, fresh and dry mass decrease; and the electrontransport chain and CO2 assimilation are also affected [78]. Furthermore, toxic compounds and ROS accumulated.…”
Section: Waterlogging Stressmentioning
confidence: 99%